PENGARUH STRES KERJA TERHADAP PRESTASI KERJA KARYAWAN PADA PT. BOSOWA BERLIAN MOTOR CABANG MAKASSAR - Andi Widiawati (AkMen JURNAL ILMIAH, 2015)
This research aims to identify and analyze the effects of job stress that consist of intrinsic factor in the work, the role of individuals in the organization, relationships within the work, demands from outside the organization / job on employee performance and to identify and analyze the work stress variables most influential on employee performance at PT. Bosowa Berlian Motor Branch Makassar. The method used in this research is quantitative method with multiple regression. The result of this research is which of the four independent variables that influence employee performance (Y) PT. Bosowa Berlian Motor Makassar branch, in the can that the most influential is the variable role of individuals in the organization (X2) based on the results of the t test variable role of individuals in the organization (X2) has tcount> ttabel most compared to other variables, with significant requirements. Thus, the second hypothesis which states alleged demands from outside the organization / job (X4) is the most dominant variable is not statistically proven